Pengaruh Persepsi Kemudahan Pengguna terhadap Minat Beli Ulang Produk Scarlett di Tiktok Shop Melalui Mediasi Emosi Positif - I Wayan Wita Merta; Nilna Muna; Made Mulyadi; Putu Ayu Titha Paramita Pika (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to explore the effect of perceived ease of use on repurchase intention through the mediation of positive emotion among Scarlett consumers on TikTok Shop. This phenomenon emerges along with the increasing penetration of social media users, which drives these platforms to function not only as entertainment media but also as transaction channels. The transformation of social media into social commerce enables users to conduct various digital activities within a single platform. This research employs a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM), implemented with SmartPLS 4.0. A purposive sampling technique was applied to obtain 128 respondents who had purchased Scarlett products via TikTok Shop. The results indicate that perceived ease of use has a positive and significant effect on repurchase intention through the mediation of positive emotion. Positive emotion is found to act as a full mediator that strengthens the relationship between the independent variable and consumers’ repurchase intention. These findings confirm that feelings of enjoyment and satisfaction during shopping make consumers more likely to repurchase. Practically, this study highlights the importance of enhancing a pleasant shopping experience to elicit consumers’ positive emotions, which in turn reinforce repurchase intention toward a product on social commerce platforms.